Gratitude and Adolescents’ Subjective Well-Being in School: The Multiple Mediating Roles of Basic Psychological Needs Satisfaction at School - Tian, Lili; Pi, Luyang; Huebner, E. S.; Du, Minmin (Frontiers in Psychology, 2016)
Based on the relationship between gratitude and general subjective well-being, and Basic Psychological Needs Theory (BPNT; Ryan & Deci, 2000), the present study's aim was to use structural equation modeling to test the multiple mediational roles of the satisfaction of three basic psychological needs at school in accounting for the association between gratitude and subjective well-being in school (school satisfaction, school affect) in adolescents. A total of 881 Chinese adolescents (427 males; Mean age = 12.97) completed a multi-measure questionnaire tapping the targeted variables. Results indicated that gratitude related statistically significantly to adolescents’ subjective well-being in school. Furthermore, a multiple-mediators analysis indicated that competence and relatedness needs satisfaction at school mediated the relation between gratitude and subjective well-being in school. Lastly, a multiple-mediators analysis also indicated that gratitude related to subjective well-being in school indirectly through autonomy needs satisfaction at school. Limitations and practical applications of the study were discussed.